Proxy Climatic Data from Tree Rings at Lake Louise, Alberta : A Preliminary Report - Luckman, B.; Hamilton, J.; Jozsa, L.; Gray, J. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTPreliminary results are presented of studies using oxygen isotopes and tree-ring densitometry to derive proxy climatic data from Picea engelmannii and Abies Iasiocarpa in the Canadian Rockies. Significant correlations occur between mean annual temperatures and δ18O determinations from five year groups of tree rings from three trees. However, unexplained anomalies in these relationships indicate that ring-width effects may reduce this correlation in some cases and that further exploratory work is necessary. Indexed chronologies for the period 1705-1980 were developed for 15 tree-ring variables derived by X-ray densitometry from 16 Picea cores. Principal components analysis was used to identify three groups of highly inter-correlated variables related to ring width, earlywood density and latewood characteristics. Each group responds differently to climatic controls increasing the potential for development of proxy climatic data over ring-width measures alone. Transfer function development is incomplete but preliminary results for summer temperature (June and July, R2 = 0,46) and December-March precipitation (R2 = 0,40) are presented as examples. Using these equations preliminary reconstructions for the period 1710-1980 are presented.